2019
DOI: 10.1111/ntwe.12155
|View full text |Cite
|
Sign up to set email alerts
|

Measuring digital platform‐mediated workers

Abstract: The role of digital platform workers, whether they are delivering fastfood or working remotely categorising photographs, has received much attention both in the media and among policymakers. However, there is a lack of comparable and consistent statistics, over time and across countries, on the number of platform workers, their characteristics and their types of jobs and tasks. This review article examines the attempts that have been made to measure the number of digital platform workers, including both tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Accurate estimates of the prevalence and social distribution of platform work are generally lacking in North America (Collins et al 2019), with a rare exception being a recent study by the Pew Research Center (Anderson et al 2021), which revealed that 16 percent of Americans reported earning income from online labor platforms at least once. Inconsistent approaches to identifying platform workers, however, means that quantitative measurement of their work conditions and personal characteristics, including their health, remains in its infancy (O’Farrell and Montagnier 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate estimates of the prevalence and social distribution of platform work are generally lacking in North America (Collins et al 2019), with a rare exception being a recent study by the Pew Research Center (Anderson et al 2021), which revealed that 16 percent of Americans reported earning income from online labor platforms at least once. Inconsistent approaches to identifying platform workers, however, means that quantitative measurement of their work conditions and personal characteristics, including their health, remains in its infancy (O’Farrell and Montagnier 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Online freelancing reflects a form of labor market that relies on mediated and fully digital interactions between these workers and potential employers. Even as O’Farrell and Montagnier, (2019) articulate difficulties with determining the scale of platform-mediated work, estimates suggest there are 56 million online freelancers globally, 40% of whom are U.S. - based ( Kässi and Lehdonvirta, 2018 ; Stephany et al, 2021 ). And, these online labor markets have grown by almost 50% since 2017 ( Kässi and Lehdonvirta, 2018 ; Stephany et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having generated a wealth of research on its work and employment conditions, as well as its disruptive impact on traditional labour markets, the prevalence and drivers of internet and platform work remain underdeveloped. A major obstacle has been the lack of comparable and representative data (O'Farrell & Montagnier, 2020; Piasna, 2020).…”
Section: Introductionmentioning
confidence: 99%